Mineral Liberation and Particle Breakage in Stirred Mills - Roufaill, Reem; Klein, B. (Canadian Institute of Mining, Metallurgy and Petroleum, 2010)
In this paper, the study of particle breakage mode versus mill operating parameters is addressed. Stirred mills grinding modes are mainly attrition but could be manipulated to include breakage by compression or impact loading. Macro and micro analysis of particle breakage and grinding mechanisms are correlated. Macro analyses convey information that relates grinding mechanism to particle size and shape. Micro analysis on the other hand relates the particle breakage mode to the fracture type whether transgranular or intergranular. Intergranular particle breakage leads to higher mineral liberation compared to transgranular breakage. Similar minerals would have more homogeneous properties that convey a stronger bond compared to dissimilar, heterogeneous mineral bonds. This paper presents the results of an investigation that assesses how operating conditions can affect trans- versus inter-granular breakage. It is deduced that with the standard stirred mill operation, the breakage mode is primarily abrasion. Breakage mode is characterized using morphology analysis as a tool. Accordingly, if mill operation is controlled such that compression and impact breakage modes are imposed, then there will be a potential to impose inter-granular breakage rather than trans-granular.